2002
DOI: 10.1006/geno.2002.6831
|View full text |Cite
|
Sign up to set email alerts
|

Ovol2, a Mammalian Homolog of Drosophila ovo: Gene Structure, Chromosomal Mapping, and Aberrant Expression in Blind-Sterile Mice

Abstract: The ovo gene family consists of evolutionarily conserved genes including those cloned from Caenorhabditis elegans, Drosophila melanogaster, mouse, and human. Here we report the isolation and characterization of mouse Ovol2 (also known as movol2 or movo2) and provide evidence supporting the existence of multiple Ovol2 transcripts. These transcripts are produced by alternative promoter usage and alternative splicing and encode long and short OVOL2 protein isoforms, whose sequences differ from those previously re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 25 publications
3
39
1
Order By: Relevance
“…Recently, Li et al (2002a) reported two MOVO isoforms, named Ovol2A and Ovol2B, by compiling sequences of PCR-amplified cDNA fragments. Sequence comparison showed that Ovol2A was almost equivalent to MOVO-A, while Ovol2B was to MOVO-C.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al (2002a) reported two MOVO isoforms, named Ovol2A and Ovol2B, by compiling sequences of PCR-amplified cDNA fragments. Sequence comparison showed that Ovol2A was almost equivalent to MOVO-A, while Ovol2B was to MOVO-C.…”
Section: Discussionmentioning
confidence: 99%
“…Ovol2 Reinduces Central Components of the GRHL2 Network and Rescues TER and Lumen Expansion in Grhl2-Deficient Cells The gene encoding OVOL2, a mammalian homolog of Drosophila ovo, 26 was among the core targets of GRHL2. Deletion of Ovol2 in mice results in an embryonic phenotype and death by E10.5, 27 similar to the phenotype observed in Grhl2 mutant mice.…”
Section: Grhl2 Is Required For Lumen Expansion and Epithelial Barriermentioning
confidence: 99%
“…4,5 OVOL2 expression has been also observed in murine and human epithelial tissues, such as skin and the germinal epithelium of the testes. 6 A molecular study of OVOL2 expression demonstrated that OVOL1 represses the activity of the OVOL2 promoter in a DNA-bindingedependent manner. 7 Furthermore, genetic deletion of OVOL1 up-regulates OVOL2 expression, leading to functional compensation by OVOL2, which suggests that OVOL1 negatively regulates OVOL2 expression.…”
mentioning
confidence: 99%